Statistical Analysis on Factors that Contribute to Post Harvest Losses of Crops in Rural Area at Nkwanta Districts, Volta Regions, Ghana - Dovlo, Michael; Kunu, Etornam Kwame; Rudin, Nur Ahmad (Universitas Negeri Gorontalo, 2021)
The study was conducted to assess the factors that contribute to post harvest losses of farm produces in the Nkwanta Districts, Volta Region, Ghana. Data was collected from 250 farmers in the district using a structured questionnaire. The last item on the questionnaire examined the level of agreement attached to various factors influencing post harvest losses in the district on a five point Likert scale. Multivariate factor analysis method was used in the analysis. The results indicated that about 87.2% of the total respondent experience of post harvest losses and there are five salient factors that influence post harvest losses. Difficulties in market accessibility related factors was the most important factor of all. Another important factors accountable for post harvest losses are lack of knowledge and technology related factors, lack of storage facilities and poor packaging, the poor road network, and labour cost. It is therefore recommended that different forms of training and information should be made available for farmers. Also, the establishment of the factories and storage facilities at farming communities should be put in place in order to reduce post harvest losses by way of processing and storage of the excess produces at the local level.